THE USE OF TIME TOKEN METHOD IN IMPROVING STUDENTS’ SPEAKING SKILL AT THE SECOND GRADE OF ISLAMIC SENIOR HIGH SCHOOL MAN BANTAENG - Andi Anugrah Mappa; Lilis Karmila (Universitas Labuhanbatu, 2022)
This research aims to find out whether or not the implementation time token method is effective to improve the students’ speaking skill in term of fluency and accuracy at the second grade of Islamic senior high school MAN Bantaeng. This research used pre-experimental method. The population of this research consists of the second grade and the sample of the research is XI IIS 2 consists of 16 students at MAN Banteng, year 2021/2022. In collecting the data, the researcher gave a speaking test there was pre-test and post-test, while to analyze the data the researcher used t-test. The result of this researcher showed that the mean score in pre-test for fluency was 1.18 and post-test was 2.9. The mean score in pre-test for accuracy was 1.43 and in post-test was 3. And the total mean score of students’ speaking skill in pre-test was 2.6 and post-test 6. The degree of freedom significance 5% was 2.131 it was higher than the result of the significance difference of the post test that was 10,088. It means that by applying time token method in teaching speaking can help in improve the students’ speaking skill. Thus, concluded that improving students’ speaking skill is significantly better after getting treatment. So the alternative hypothesis is accepted and the null hypothesis is rejected. Therefore, it is proven that time token method can improve the students’ speaking skill.